2019
DOI: 10.1186/s12903-019-0793-6
|View full text |Cite
|
Sign up to set email alerts
|

Link between perceived oral and general health status among Yemeni adult dental patients

Abstract: Background Self-perceived health is an essential measure of health status and even a paramount predictor of mortality. So long as it is said that oral health (OH) and general health (GH) are mirrors to each other. This study sought to determine how Yemeni adults rate their OH and GH, whether such a self-rating influenced by some potential risk factors, and whether both ratings (OH and GH) are correlated. Methods A sample of 587 Yemeni dental patients aged 20 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(57 reference statements)
3
8
1
1
Order By: Relevance
“…Adolescents who reported fair/poor oral health were more likely to also report fair/poor general health and quality of life. A study in Yemen found that people who perceived their general health as very good/excellent were also likely to perceive their oral health as very good/excellent [25]. Our results further indicated that adolescents who reported having toothache, bleeding gums, and were unhappy with the appearance of their teeth were more likely to report their oral health status as fair/poor.…”
Section: Discussionsupporting
confidence: 71%
“…Adolescents who reported fair/poor oral health were more likely to also report fair/poor general health and quality of life. A study in Yemen found that people who perceived their general health as very good/excellent were also likely to perceive their oral health as very good/excellent [25]. Our results further indicated that adolescents who reported having toothache, bleeding gums, and were unhappy with the appearance of their teeth were more likely to report their oral health status as fair/poor.…”
Section: Discussionsupporting
confidence: 71%
“…A study in Yemen found out that people who perceived their general health as very good/excellent were also likely to perceive their oral health as very good/excellent. [21] Our results further indicated that adolescents who reported having toothache, bleeding gums, and were unhappy with the appearance of their teeth, were more likely to report their oral health status as fair/poor. Similar results have been reported by David et al in a 2006 study in Kerala, India, where self-reported oral status was found to be related to appearance of teeth and caries experience.…”
Section: Discussionsupporting
confidence: 63%
“…Several systemic diseases have oral manifestations and have different effects on general health. Improved oral hygiene reduces the progression or occurrence of periodontal disease, characterized by the destruction of the supporting tissues of the tooth [3] and it prevents respiratory disease among high-risk elderly adults living in nursing homes and patients in intensive care units. Studies support the significance of oral and dental factors while controlling for established medical risk factors in chronic bronchitis, pneumonia, and chronic pulmonary obstructive disease [4,5,6].…”
Section: Introductionmentioning
confidence: 99%